Allele mining for resistance gene analogs (RGAs) in crop plants: A special emphasis on blast resistance in finger millet (Eleusine coracana L.) - Kumar, Anil; Babu, B. Kalyana; Yadav, Shambhavi; Agrawal, Pawan K. (The Indian Journal of Genetics and Plant Breeding, 2016)
Finger millet a nutritionally rich underutilized crop requires more attention of research community. One of the major limitations of finger millet for wider agronomic acceptability is because of its susceptibility to blast fungus Magnaporthe grisea, which is also the causative agent of blast in rice. A large amount of sequence data available in the public domain has facilitated identification and isolation of novel genes for blast resistance and other agronomically important traits. Availability of such large genomic data has made allele mining a viable approach for detecting novel alleles for blast resistance in finger millet. However, very scarce genomic information is available in finger millet, being the major hurdle for such approaches. In the present review, we have summarized different strategic approaches suitable for allele mining of resistance gene analogs (RGAs) in finger millet by utilizing the large sequence data available for rice through comparative genomics. This paves the way for transfer of blast alleles into high yielding, blast susceptible and locally well adapted germplasm through molecular breeding and genetic engineering approaches.